Handbook of clinical interviewing with adults - Hersen, Michel; Thomas, Jay C., 1951- (Sage Publications, 2007)
This handbook is one of three interrelated titles on the topic of interviewing for specific populations. It presents a combination of theory and practice plus concern with diagnostic entities for readers who work, or one day will work, with adults in clinical settings.